PROBLEMS OF TAXATION IN THE DIGITAL ECONOMY WITHIN THE EURASIAN ECONOMIC UNION - A. Bezverkhii; E. Kirova (Вестник университета, 2019)
The article identifies the main problems of taxation in the digital economy in the countries of the Eurasian Economic Union. The authors specify the concept of digital economy. The problems of taxation of e-Commerce in the Eurasian Economic Union countries have been revealed. It has been proposed to consolidate the concept of e-Commerce in the tax legislation of the Eurasian Economic Union countries, as well as the application of new technologies to identify electronic transactions through using of modern tools. In order to implement the principle of certainty of taxation, a scheme for determining the location of the end user of electronic services has been developed. Possible ways to solve the problems of taxation caused by the application of business models of the digital economy have been proposed.